Suppress the diffusion of rumors with nodes closeness mining - Ya-ping TIAN; Li YANG; Xiao-qin WANG; Ya-feng QIAO (网络与信息安全学报)
Through making the analysis of information spread in social networks,the supression of rumors,error information and other negative information was realized.Firstly,by analyzing the structure of social networks and the characteristics of node behavior,a method for the identification of opinion leader nodes was proposed based on the degree of intimacy between nodes in social networks.Then,the rumor propagation model and the analysis of nodes’ state transformation process were made when the rumor spread in social networks.At last,the control method was proposed to suppress the diffusion of rumors with the nodes’ closeness.